PENGGUNAAN KATA BAHASA JAWA DALAM PARIKAN YANG TERDAPAT PADA PENTAS WAYANG KULIT DI KABUPATEN CILACAP - Ratna Khoirun Nisa; Nusarini Nusarini (Universitas Sarjanawiyata Tamansiswa, 2016)
The purpose of this study describes the form of Java language Java language words contained parikan at the wayang puppet stage and describe the Java language word classes contained in parikan at the wayang puppet stage. The research is a qualitative research. The data obtained in the form used by the NII parikan puppeteer and puppet performances sinden on the skin. Source of this research is recording the puppet show as well as interviews with the puppeteer and sinden. Data obtained using the method of observation to see the techniques involved free conversation, record, record and interview method with fishing techniques and advanced techniques capable semuka. Data were analyzed with methods of unified referential. Presentation of the results of the analysis of this study is to use the model of informal data presentation. Results of this study are as follows. (1) The form of words contained in the Java language parikan at the leather puppet stage is (a) a base or tembung lingga (word phallus) (b) the word derivative / tembung andhahan, covering affixed words, repeated words / tembung rangkep and process composition / camboran (2 ) Class Javanese tembung kriya word contained in parikan at the wayang puppet stage were (a) noun / noun (tembung aran) (b) verb / verbs (tembung kriya) (c) adjective / adjective (tembung kaanan) (d ) adverb / adverb, (tembung katrangan) (e) pronoun / pronouns (tembung sesulih) (f) said numbers / numeralia (tembung wilangan) (g) conjunctions / conjunctions (tembung panggandeng) (h) said callers, interjection (tembung panguwuh).